The WTO Global Trade Costs Index and its determinants - Stela Rubínová; Mehdi Sebti (World Trade Organization (WTO), 2021)
This study provides a decomposition of the WTO Global Trade Costs Index into five policy-relevant components: transport and travel costs; information and transaction costs; ICT connectedness; trade policy and regulatorydifferences; and governance quality. The WTO Global Trade CostsIndex is based on a new methodology by Egger et al. (2021) that delivers directional trade cost estimates and sector-specific elasticities whichare crucialforinferring tradecostsfromtradeflows data. Theresulting measure of trade costs includes all factors that burden foreign sales more than domestic ones. In this study, we run a sectoral regression analysis to determine what drives trade costs variation across partners and use the resultstodecompose the variation in trade costsin eachsector. We show that transport and travel costs play the most important role in overall trade costs both for goods and services. Tradepolicy and regulatorydifferences are the second major component of trade costs in most sectors, accounting for at least 14%. The importance of this component is particularly striking for trade among lower-income economies. Moreover, our results alsoshow that trade policy in services sectors matters for trade costs in goods, and vice versa. Finally, we find that access to information and communication technology is especially important for tradecostsin services where its importance hasincreasedover time, highlighting the role that digitaldelivery plays in this sector.
Keywords: F10; F14; F15; 330; Trade costs; gravity model; non-tariff barriers; trade integration; trade elasticity